ORGANISASI MAHASISWA ISIMU PACITAN DALAM MEMBENTUK SOFT SKILL DIRI - Hamdani, Mohammad Khusnul; Prahastiwi, Eka (Pimpinan Cabang Muhammadiyah Kramat Jati, 2022)
In this day and age, one's expertise is needed according to one's talents, especially soft skill development. Soft skills have a role in a person in acting and innovating. The ISIMU Pacitan student organization teaches various competencies and trains skills in being creative and innovating in solving problems. The campus provides ample space for organizations to develop students' talents and interests in training personal soft skills. Students with bad habits such as geam, touring, hanging out can be diverted to participate in student organization activities that have a positive charge on self-development. This research analyzes the data using data presentation, data reduction to drawing conclusions. If valid, this research has a correlation with the soft skills of students who have contributed to self-development